Evaluation of INIA real sicaina and shulay potato varieties for industrial processing as frozen pre-fried potatoes: a case study for the peruvian agro-industry - Castañeda Ortiz, Eva Danae (2024)
The study evaluated the INIA Real Sicaina and Shulay potato varieties for processing as frozen pre-fried potatoes, given the growing interest in the Peruvian agroindustry. These varieties were compared with imported ones under blanching and pre-frying treatments, highlighting the lack of prior research on local varieties. The main challenge lies in Peru's technological gap, where frozen pre-fried potatoes are not produced due to raw material quality and limited processes. This research tested new varieties and analyzed the impact of treatments on key indicators like color and moisture. The results showed that these varieties have the potential to meet industrial standards, especially under HTST treatment, with the Real Sicaina variety achieving comparable quality levels to imported varieties. This work promotes the development of the Peruvian agroindustry, providing a foundation for future research on optimized processes and new potato-based products.